Sistem Pendukung Keputusan Prioritas Pembelian Barang Menggunakan Metode Simple Addtive Weighting (Studi Kasus: PT. Atlindo) - Adimas Fikri Ramadhani; Kamal Prihandani; Dadang Yusup (Peneliti.net, 2021)
Along with the times, the development of information technology also develops and brings many changes in various aspects. With the development of information technology affects people's lives. Utilization of technology can now also be felt in various fields, one of which is in the business sector. PT. Atlas Lintas Indonesia (ATLINDO) wants to utilize information technology in order to work more efficiently and improve the quality of the company. The information technology that wants to be used is a decision support system to get the priority of purchasing goods. So that it can help the company in meeting the needs of goods. This application was developed using the SDLC method with the Waterfall model and using the Simple Additive Weighting method in making decisions. This application was developed with the feature of managing goods or alternative data, then what criteria are needed, and printing reports on the results of the decisions made.